Industrial plastics : - Lokensgard, Erik (Thomson Delmar Learning, 2004)
Current technologies and manufacturing methods are the keystone for this introduction to all facets of the plastics industry, highlighted by an extensive art program. Complete up-to-date coverage and graphics are further augmented by practical lab activities that build on the topics covered in the chapters, involving students in hands-on learning to strengthen the link between theory and practice. Topics covered include plastics recycling, ISO and ASTM testing specifications, and current health and safety standards. It is this broad coverage of the developments in materials and processes affects our daily lives that makes Industrial Plastics an outstanding resource for students and professionals alike.